2006
DOI: 10.1088/0264-9381/23/7/011
|View full text |Cite
|
Sign up to set email alerts
|

Frame dragging, vorticity and electromagnetic fields in axially symmetric stationary spacetimes

Abstract: Abstract. We present a general study about the relation between the vorticity tensor and the Poynting vector of the electromagnetic field for axially symmetric stationary electrovacuum metrics. The obtained expressions allow to understand the role of the Poynting vector in the dragging of inertial frames. The particular case of the rotating massive charged magnetic dipole is analyzed in detail. In addition, the electric and magnetic parts of the Weyl tensor are calculated and the link between the later and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 33 publications
3
61
0
Order By: Relevance
“…We must stress at this point that this is an observer dependent effect (as it should be because we are dealing with an inertial force) which manifests itself in the fact that the angular velocity of the gyroscope depends on the observer. An effect similar to this was pointed out in a particular case in [12] and this was latter confirmed in [22]. In the former reference it was shown that gyroscopes placed in the spacetime generated by a nonrotating charged magnetic dipole would precess.…”
Section: Coupling Of the Vorticity And The Poynting Vectorsupporting
confidence: 61%
“…We must stress at this point that this is an observer dependent effect (as it should be because we are dealing with an inertial force) which manifests itself in the fact that the angular velocity of the gyroscope depends on the observer. An effect similar to this was pointed out in a particular case in [12] and this was latter confirmed in [22]. In the former reference it was shown that gyroscopes placed in the spacetime generated by a nonrotating charged magnetic dipole would precess.…”
Section: Coupling Of the Vorticity And The Poynting Vectorsupporting
confidence: 61%
“…This may have the following two explanations: firstly, the formula (28) of [1] defining S ϕ is not quite appropriate for concrete applications, even in the simplest cases such as Manko's solution [3] for a magnetized Kerr-Newman mass utilized in [1]. And, secondly, the determinantal form of writing specific exact solutions employed in [1] only permits to arrive at some formal expressions which need to be further simplified by expanding the determinants.…”
Section: Introductionmentioning
confidence: 99%
“…To make things worse, it appears that the determinantal expressions of [1] which are entirely taken over from the paper [4] devoted to the multisoliton electrovac solution, are all presented with errors, including the definitions of the quantities h l (α n ). Such distorted formulae can be neither reproduced nor used in any physical analysis; neither they can be considered as a substitute to the elegant original formulae defining Manko's electrovac solution [3].…”
Section: Introductionmentioning
confidence: 99%
“…He then suggests that such a circular flow of energy affects inertial frames by producing vorticity of congruences of particles, relative to the compass of inertia. Later, this conjecture was shown to be valid for a general axially symmetric stationary electrovacuum metric [19].…”
Section: Introductionmentioning
confidence: 93%